Antagonizing FcαR1 (CD89) as treatment in IgA-mediated chronic inflammation and autoimmunity - van Delft, Myrthe A. M.; Aleyd, Esil; Mast, Richard van der; de Jong, Niels; Boon, Louis; Simons, Peter J.; van Egmond, Marjolein (Frontiers in Immunology, 2023)
Immunoglobulin A (IgA) is mostly considered as a non-inflammatory regulator at mucosal areas. However, previous work of our group showed that IgA can also be involved in disease pathology, because it provides a potent stimulus to activate neutrophils after crosslinking of surface CD89 (FcRI), resulting in chronic inflammation and tissue damage. IgA (auto)antibodies and neutrophils are key players in various diseases, including blistering skin diseases and rheumatoid arthritis. Therefore, we generated an array of anti-CD89 monoclonal antibodies (mAbs) for therapeutic targeting of CD89. The biological activity of newly developed anti-human CD89 mAbs and their potential therapeutic capacity were investigated. Flow cytometry showed that all generated anti-CD89 mAbs bound surface CD89 on neutrophils. Isolated neutrophils were incubated with IgA-coated beads and activation was determined in the presence or absence of anti-human CD89 antibodies. Although these anti-CD89 mAbs bind to different epitopes on EC1 of CD89, they all have the capacity to inhibit IgA-mediated phagocytosis, neutrophil extracellular trap (NET) release and neutrophil migration. Moreover, IgA-mediated leukotriene B4 and lactoferrin release are decreased in supernatant from anti-CD89 mAbs-treated neutrophils. Finally, anti-CD89 mAb clone 10E7, that was selected based on its selective binding profile on tissue micro arrays, reduced anti-mouse collagen XVII hIgA-induced neutrophil influx in an in vivo linear IgA bullous disease (LABD) mice model. This study clearly indicates that our newly developed anti-CD89 mAbs inhibited IgA-induced neutrophil activation and reduced anti-autoantigen IgA-induced neutrophil influx in vivo, supporting further clinical development for the treatment of LABD.